2012
DOI: 10.1182/blood-2011-06-358564
|View full text |Cite
|
Sign up to set email alerts
|

The Sumo-targeted ubiquitin ligase RNF4 regulates the localization and function of the HTLV-1 oncoprotein Tax

Abstract: The Really Interesting New Gene (RING) Finger Protein 4 (RNF4) represents a class of ubiquitin ligases that target Small Ubiquitin-like Modifier (SUMO)-modified proteins for ubiquitin modification. To date, the regulatory function of RNF4 appears to be ubiquitin-mediated degradation of sumoylated cellular proteins. In the present study, we show that the Human T-cell Leukemia Virus Type 1 (HTLV-1) oncoprotein Tax is a substrate for RNF4 both in vivo and in vitro. We mapped the RNF4-binding site to a region adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…Furthermore, we show here that fusion of SUMO-1 stabilizes both Tax and Tax-P79AQ81A in the cytosol but only significantly increases ubiquitination of Tax-P79AQ81A. This latter effect is reminiscent of the cytoplasmic relocalization and enhanced ubiquitination of the GFP-tagged Tax construct upon RNF4 overexpression [27]. Why RNF4 would only increase the ubiquitination of Tax mutants but not wt Tax remains to be elucidated.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, we show here that fusion of SUMO-1 stabilizes both Tax and Tax-P79AQ81A in the cytosol but only significantly increases ubiquitination of Tax-P79AQ81A. This latter effect is reminiscent of the cytoplasmic relocalization and enhanced ubiquitination of the GFP-tagged Tax construct upon RNF4 overexpression [27]. Why RNF4 would only increase the ubiquitination of Tax mutants but not wt Tax remains to be elucidated.…”
Section: Discussionmentioning
confidence: 88%
“…It has also been shown that the SUMO-dependent ubiquitin ligase, Really Interesting New Gene Finger Protein 4 (RNF4), binds to SUMOylated Tax next to the Lys280/Lys284 ubiquitin and SUMO modification sites and ubiquitinates the nuclear located protein. The ubiquitination of Tax by RNF4 leads to the cellular translocation of Tax to the cytoplasm and subsequently increases NF-κB activation while decreasing Tax activity associated with interaction with nuclear CREB (Fryrear et al, 2012). Ubiquitination of Tax at lysine residues 263, 280, and 284 is also required for Tax assisted localization of IKKγ to the Golgi (Harhaj et al, 2007).…”
Section: Tax Both Undergoes and Promotes Post-translational Modificationmentioning
confidence: 99%
“…Moreover, STUbL-mediated ubiquitylation does not only target proteins for degradation. For example, STUbL-mediated ubiquitylation affects the affinity of protein-protein interactions, which, in turn, affects subcellular localization, as well as enhances transcriptional activation (Fryrear et al, 2012; Poukka et al, 2000; Hu et al, 2010). Previously, we showed that Dgrn, the sole Drosophila STUbL protein, inactivates the SUMOylated co-repressor Groucho/Transducing-like enhancer of split (Gro/TLE) and inhibits Gro-dependent gene repression in vivo (Abed et al, 2011).…”
Section: Introductionmentioning
confidence: 99%